THE BEHAVIORAL STUDY OF PSYCHOLOGICAL DEVELOPMENT - Umarkhodjaeva Muminakhon Saidturayevna (World Scientific Research Journal, 2025)
Introduction. Psychology is the scientific study of human behavior, thoughts, emotions, and development. Among the various approaches in psychology, behaviorism holds a significant place. Behaviorism focuses on explaining behavior based on external stimuli and learning processes, arguing that all human behaviors are shaped by the environment rather than internal mental states.